Extensional deformation along the Footwall Fault below the Hyde-Macraes Shear Zone, Otago Schist, New Zealand. Issue 2 (3rd April 2018) - Ring, Uwe; Mortimer, Nick; Butz, Christoph; Bernet, Matthias
ABSTRACT: We describe ductile-to-brittle structures across the Footwall Fault directly below the Hyde-Macraes Shear Zone in the Otago Schist. These indicate that pervasive deformation along the Footwall Fault was due to northeast–southwest crustal extension. Structures below the Footwall Fault are ductile top-to-the-northeast extensional shear bands that formed in a penetrative lower greenschist facies foliation. With progressive deformation, shear bands formed at higher angles to the foliation, culminating in the shear bands being cut by low- and high-angle normal faults. In the hanging wall, extensional structures are much less pervasive and comprise a few high-angle normal faults. This sharp contrast in structural evolution of footwall and hanging wall resembles the tectonic evolution of major extensional shear zones worldwide. We propose that mid Cretaceous normal movement on the low-angle Footwall Fault accompanied the formation of the steeper Waihemo Fault further north. On a regional scale, much of the boundary between the Otago Schist core and its northern flank is cut by mid Cretaceous normal faults. Zircon fission-track ages from the footwall range from 79 ± 13.7 to 46.1 ± 6.2 Ma (2σ uncertainties) and young in the direction of hanging wall transport. One sample from the hanging wall yielded a zircon fission-track age of 76 ± 12.9 Ma. The fission-track ages are hard to interpret as zircon across the fault zone was affected by partial or full annealing. In part, the ages confirm mid Cretaceous movement but may also be interpreted to suggest additional reactivation of the Footwall Fault at slow inferred slip rates.